Factors Associated with Morbidity and Mortality of Goat in Extensive and Semi-Intensive Farming Systems in the Eastern Province of Sri Lanka (Journal of the Bangladesh Agricultural University, 2024)
The present study was conducted to identify the associated factors with morbidity and mortality of goats in extensive and semi-intensive farming systems. A sample of 266 goat farmers of three districts i.e., Ampara, Batticaloa and Trincomalee in the eastern province were randomly selected with the assistance of veterinary offices. A pre-tested questionnaire with face-to-face interviews, farm visits and observations were used to collect the data. The study found that goat farming is a male-dominant (>90%) activity regardless of the farming systems. Young and middle-aged farmers with better educations adopted semi-intensive farming systems while the older and poorly educated farmers adopted extensive farming systems while being self-employed. The factors i.e., ectoparasites, lack of feed, lack of water, age of the goats, rainy season, and the lack of veterinary services significantly associated (p